Managing melon weevil of sponge gourd - Halder, Jaydeep; Kushwaha, Deepak; Rai, A B; Chaube, T; Singh, B (Indian Horticulture, 2019)
Luffa, L. cylindrica, a member of cucurbitaceae family, commonly known as sponge gourd or vegetable sponge is grown throughout India but more widely in the Indo-Gangetic plains of Uttar Pradesh, Bihar and Jharkhand. Apart from its wide use as a vegetable in various ways as curry, chutney, sambhar or eaten raw like cucumber, its fruit is also used in traditional medicine as anthelmintic, carminative, laxative, depurative, emollient, expectorant, diuretic and lactagogue. It is also useful in treatment of fever, syphilis, tumours, bronchitis, splenopathy and leprosy. There is a huge demand of this crop thoroughout the year in this region, and India ranks first in sponge gourd production in the world.